2003
DOI: 10.4049/jimmunol.170.8.4161
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the TCR β Variable Gene Repertoire in Chimpanzees: Identification of Functional Homologs to Human Pseudogenes

Abstract: Chimpanzees are used for a variety of disease models such as hepatitis C virus (HCV) infection, where Ag-specific T cells are thought to be critical for resolution of infection. The variable segments of the TCR αβ genes are polymorphic and contain putative binding sites for MHC class I and II molecules. In this study, we performed a comprehensive analysis of genes that comprise the TCR β variable gene (TCRBV) repertoire of the common chimpanzee Pan troglodytes. We identified 42 P. troglodytes TCRBV sequences r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…We determined the structure of the epitope-specific TCR repertoire by sequencing ex vivo-purified HIV-specific CD8 ϩ T cells and by staining with a panel of monoclonal antibodies specific for 24 V␤ regions as previously described. 1,4,6,40 A recent study reported preferential V␤ 13.2 gene usage by B8-FL8-specific CD8 ϩ T cells in subjects maintaining CD4 counts more than 500 for longer than 8 years. 46 Although we observed an overrepresentation of certain V␤ regions within the epitope-specific TCR repertoire, most of our subjects used structurally diverse TCRs with different V␤ regions and with high amino acid diversity within the antigen recognition site of TCR␤ chains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the structure of the epitope-specific TCR repertoire by sequencing ex vivo-purified HIV-specific CD8 ϩ T cells and by staining with a panel of monoclonal antibodies specific for 24 V␤ regions as previously described. 1,4,6,40 A recent study reported preferential V␤ 13.2 gene usage by B8-FL8-specific CD8 ϩ T cells in subjects maintaining CD4 counts more than 500 for longer than 8 years. 46 Although we observed an overrepresentation of certain V␤ regions within the epitope-specific TCR repertoire, most of our subjects used structurally diverse TCRs with different V␤ regions and with high amino acid diversity within the antigen recognition site of TCR␤ chains.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,6,40 In subjects AC-14 and AC-15, 6 and 7 different clonotypes, respectively, could be detected within the B8-FL8-specific CD8 ϩ TCR repertoire. Most CDR3 amino acid sequences were heterogenous, and there was no common motif detectable throughout the sequences.…”
Section: Structural Diversity Of Immunodominant Hiv-specific Cd8 ؉ T mentioning
confidence: 98%
“…In addition to amino acid substitution, divergence at a transcriptional level, such as cis-regulated gene expression divergence and the gainand-loss of genes, is likely to be an important factor in the genomic evolution of organisms to create phenotypic complexity (King and Wilson, 1975;Enard et al, 2002a;Heissig et al, 2005;Marques et al, 2005;Rockman et al, 2005). Although gains-and-losses of genes might cause a larger phenotypic effect than single amino acid substitutions (Olson and Varki, 2003), fewer studies have described lineage-specific gains-and-losses of genes among higher primates (Chou et al, 1998;Stedman et al, 2004;Hahn and Lee, 2005;Hayakawa et al, 2005;Wang et al, 2006), with the exception of the frequent births and deaths of genes in large multi-copied gene families (Meyer Olson et al, 2003;Fortna et al, 2004;Gilad et al, 2005;Go et al, 2005). Using the human and chimpanzee genome sequence, we could conduct a genome-wide survey of species-specific pseudogenes, which carry null mutations in the coding region either in the human and chimpanzee (Hahn and Lee, 2005;Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…The diversity of the TCR CDR3 region was determined using the Shannon entropy index (H) (31,49) calculation for protein sites as described previously (53), using the formula H ϭ Ϫ⌺p i log 2 p i , where p i is the fraction of residues at a site that is amino acid type i. For amino acids in the CDR3 region, H can range from 0 (site contains only one amino acid in all sequences) to 4.32 (all amino acids are represented equally at this site).…”
Section: Methodsmentioning
confidence: 99%